Commercial temptation: Cross-border radio and the comparative transformation of public service broadcast policy in Britain, South Africa and India, 1930–67. (1st April 2017) - Jenks, John
Britain pioneered the idea of broadcasting as a commercial-free and culturally uplifting monopoly, which its imperial progeny in South Africa and India adopted. But all three soon found themselves vulnerable to entrepreneurs broadcasting commercials and pop culture from accommodating locations just across national frontiers. Listeners in all three countries tuned in by the millions and advertisers rushed to sponsor shows and buy commercials. Radio Luxembourg outdrew the British Broadcasting Corporation on Sundays in the 1930s, Radio Ceylon easily bested All India Radio in the 1950s, and Lourenço Marques Radio dominated the white South African youth market in the 1960s. Governments tried to fight the cross-border broadcasters through diplomacy, economic pressure and petty harassment, but in all cases popular 'light' culture and, eventually, advertising prevailed. This article details the common experiences and connections among these broadcasters, and points the way for future research.